2022
DOI: 10.1186/s12885-022-10379-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in individuals with advanced gastrointestinal stromal tumor treated with ripretinib in the fourth-line setting: analysis from the phase 3 INVICTUS trial

Abstract: Background Ripretinib is a novel switch-control kinase inhibitor that inhibits KIT and PDGFRA signaling. In the INVICTUS phase 3 trial, ripretinib increased median progression-free survival and prolonged overall survival vs. placebo in ≥ fourth-line advanced GIST. Here, we report prespecified analysis of quality of life (QoL) as assessed by patient-reported outcome (PRO) measures and an exploratory analysis evaluating the impact of alopecia on QoL. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Ripretinib is generally well tolerated based on both recorded toxicities [ 5 , 6 ] and, importantly, on patient-reported quality-of-life questionnaires [ 18 , 19 ]. Interestingly, toxicities of grade 3 or higher were less frequent in the BD group.…”
Section: Discussionmentioning
confidence: 99%
“…Ripretinib is generally well tolerated based on both recorded toxicities [ 5 , 6 ] and, importantly, on patient-reported quality-of-life questionnaires [ 18 , 19 ]. Interestingly, toxicities of grade 3 or higher were less frequent in the BD group.…”
Section: Discussionmentioning
confidence: 99%
“…Selfassessment of health status using the VAS EQ-5D-5L questionnaire in patients receiving ripretinib showed an increasing trend, while it decreased in the placebo group [48]. Patients treated with ripretinib assessed their physical functioning as improving, while patients from the placebo group reported its deterioration [48,49]. In summary, patients receiving ripretinib showed a statistically significant improvement in general health and QoL compared to patients receiving placebo, which showed that ripretinib, apart from favorable PFS and OS, also showed a favorable safety profile [48].…”
Section: Phase III Invictus Trialmentioning
confidence: 99%
“…An additional value of ripretinib is its effectiveness in KIT and PGDFRA wild-type GIST patients [ 82 ]. Ripretinib also resulted in a higher quality of life compared to the placebo (nominal p < 0.01) [ 83 ]. For a subset of patients who progressed in the INVICTUS trial, a dose escalation of ripretinib was allowed (2 × 150 mg daily dose).…”
Section: Fourth-line Treatment Of Metastatic or Unresectable Gistmentioning
confidence: 99%